A Review on Osmotic Dehydration Technique and its scope in startup industries. - Sriraaman M, Meenakshi M, Dr. J. KaligaRani (International Journal of Modern Agriculture, 2021)
Fruits and vegetables are the most important part of our daily life. The largest producer of fruits and vegetables in the world is India. Processing of foods by drying is one of the ancient technologies with many benefits. But, it also has many issues such as loss of quality of the product and more time consumption. To overcome these issues osmotic dehydration process can be adopted before drying the food product. Osmotic dehydration is dipping the cellulosic food material inside a solution containing solids. The pressure difference is the driving force for dehydration in this process. This osmotic dehydration technique reduces production cost, production time and also improves the quality of the product. In this context osmotic dehydration, osmotic agent, applications and factors influencing osmotic dehydration has been discussed briefly.